Hubungan Pola Asuh Orang Tua dengan Kejadian Stres pada Mahasiswa Fakultas Kedokteran - Salwa Siti Salsabila; Caecielia Makaginsar; Raden Ganang Ibnusantosa (Bandung Conference Series: Medical Science, 2023)
Abstract. Parenting styles play a role in child development, one of which is authoritarian parenting. Authoritarian parenting can make children have a lot of pressure that causes stress. This study aims to analyze the relationship between parenting style and stress events in students of the Faculty of Medicine at the Islamic University of Bandung class of 2019. The research was conducted using an analytic observational design using a cross-sectional study. The research subjects were calculated using the formula for estimating the proportion of a population. There were 110 research subjects out of a total population of 178 people who met the inclusion and exclusion criteria and were selected using a non-probability sampling technique. Retrieval of parenting pattern data using the PAQ questionnaire and stress using DASS-42. Data processing used the Chi-square test with a significance degree of 0.05. The results showed that 80 people (72.7%) had parents with authoritative parenting styles and 68 people (61.3%) had normal stress levels. Statistical results show that there is no relationship between parenting style and stress events in Bandung Islamic University Medical Faculty students class of 2019 with a P value of 0.663 (p> 0.05). This research shows that there are other factors that have more influence on stress in students of the Faculty of Medicine, Islamic University of Bandung class of 2019, such as a heavy academic load and high competition between students of the Faculty of Medicine. Abstrak. Pola asuh orang tua berperan pada perkembangan anak, salah satunya yaitu pola asuh otoriter. Pola asuh otoriter dapat membuat anak memiliki banyak tekanan yang menyebabkan stres. Penelitian ini bertujuan untuk menganalisis hubungan pola asuh orang tua dengan kejadian stres pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung angkatan 2019. Penelitian dilakukan dengan desain observasional analitik menggunakan studi cross-sectional. Subjek penelitian dihitung dengan menggunakan rumus estimasi proporsi sebuah populasi. Subjek penelitian berjumlah 110 orang dari total populasi 178 orang yang memenuhi kriteria inklusi dan eksklusi serta dipilih dengan teknik non-probability sampling. Pengambilan data pola asuh orang tua dengan menggunakan kuesioner PAQ dan stres menggunakan DASS-42. Pengolahan data menggunakan uji Chi-square dengan derajat kemaknaan 0,05. Hasil penelitian menunjukkan bahwa sebagian besar responden memilki orang tua dengan pola asuh otoritatif sebanyak 80 orang (72,7%) dan memiliki tingkat stres normal sebanyak 68 orang (61,3%). Hasil statistik menunjukan bahwa tidak terdapat hubungan pola asuh orang tua dengan kejadian stres pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung angkatan 2019 dengan P value 0.663 (p>0,05). Penelitian ini menunjukan terdapat faktor lain yang lebih berpengaruh terhadap stres pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung angkatan 2019 seperti beban akademik yang berat dan persaingan yang tinggi antar mahasiswa Fakultas Kedokteran.